Sodium and potassium intakes and adiposity among Iranian pre-adolescents and adolescents: a cross-sectional study - Golpour-Hamedani, Sahar; Rafie, Nahid; Pourmasoumi, Makan; Morteza Safavi, Sayyed; Mohammadifard, Noushin (Nutrition journal, 2022)
High sodium and low potassium intakes are associated with the early development of chronic diseases (e.g., hypertension, obesity). Taking into account the limited data on sodium and potassium intakes by 24-h excretion in urine in pre-adolescents and adolescents, we wished to determine baseline salt intake in Iranian subjects aged 11-18 years. This was an observational study involving 374 pre-adolescents and adolescents (154 boys and 220 girls). Sodium and potassium intakes were ascertained by measuring sodium and potassium excretion in urine over 24 h. Creatinine level was used to validate the completeness of the urine collections. The association between sodium and potassium intake and adiposity was determined based on body fat percentage. The mean 24-h urine sodium concentration was 3130 ± 2200 mg/day, equal to 7.961 ± 5.596 g/day salt intake. Approximately half of the study participants exceeded the upper limit of Na intake. The mean potassium intake was estimated 1480 ± 1050 mg/day. There was a positive association between urinary sodium excretion and adiposity in crude (OR 1.79; 95% CI: 1.08-2.74) and full adjusted model (OR: 3.15; 95% CI: 2.28-4.63). Also, in subsample analysis, there was a positive correlation between urinary sodium and adiposity in both pre-adolescents (OR: 2.71; 95% CI: 2.29-3.93) and adolescents (OR: 3.55; 95% CI: 2.17-4.74). However, no significant association was found between 24-h urinary potassium and adiposity. Sodium intake, as estimated by 24-h urinary excretion, was higher than recommended and it was positively associated with adiposity. Also, this study reported low compliance of potassium intake recommendations in 11-18 years' Iranian pre-adolescents and adolescents. Health promotion interventions are needed in order to broaden public awareness of high sodium intake and potassium inadequacy to reduce chronic diseases.